2023
DOI: 10.3389/ijph.2023.1605433
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Obesity With Growth and Puberty in Children: A Cross-Sectional Study in Fuzhou, China

Abstract: Objectives: To investigate the associations of obesity with growth and puberty in children.Methods: From November 2017 to December 2019, height, weight, and Tanner stages of 26,879 children aged 3–18 years in Fuzhou, China were assessed.Results: The obese group was significantly taller than the non-obese group after age 4 years for both genders, yet there was no significant difference in height between obese and non-obese group after 15.5 years old for boys and 12.5 years old for girls. The inflection points o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Previous epidemiological studies and genetic evidence have consistently indicated a causal association between obesity in girls and earlier puberty onset [ 7 , 8 , 10 , 42 , 43 , 44 ]. Our study confirmed that childhood obesity and increased BMI contributed to a younger age of menarche and increased Tanner stage in girls, offering further support for these conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous epidemiological studies and genetic evidence have consistently indicated a causal association between obesity in girls and earlier puberty onset [ 7 , 8 , 10 , 42 , 43 , 44 ]. Our study confirmed that childhood obesity and increased BMI contributed to a younger age of menarche and increased Tanner stage in girls, offering further support for these conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have linked obesity to the onset of puberty [ 7 ], although this association remains controversial. Most of the evidence from case–control, cross-sectional, and longitudinal studies has shown that childhood obesity, higher body fat percentage, and body mass index (BMI) are strongly associated with increased Tanner stage, early menarche age, and risk of precocious puberty in girls [ 8 , 9 , 10 ]. However, the rate of pubertal development was found to be decelerated in girls with obesity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics analysis may reveal important biological pathways in the pathophysiology of children with overweight and obesity and reconcile the existing conflicting evidence in children. Ying Zhang et al found that obesity had an obvious influence on growth in both genders; the obesity group was significantly taller than the nonobesity group after 4 years of age [12]. Therefore, in this study, 473 children were divided…”
Section: Introductionmentioning
confidence: 89%
“…This is consistent with the previous studies. Ying Zhang et al showed that obesity children were taller with advanced BA in early childhood, and earlier onset of puberty [39]. Akridge et al showed that the BAD of obese children aged 9-12.9 years was 1.60 years, while that of obese children aged 13-15.5 years was 0.69 years [40].…”
Section: Risk Of Advanced or Delayed Ba Developmentmentioning
confidence: 99%